Participation in multicriteria decision support - the case of conflicting water allocation in the Spree River basin - Frank Messner; Oliver Zwirner; Matthias Karkuschke (UFZ-Umweltforschungszentrum Leipzig-Halle, 2003)
This discussion paper presents the Integrated Methodological Approach for participatory multi-criteria decision support under uncertainty (IMA), which emerged from the debates about participation, multi-criteria analysis (MCA) and benefit-cost analysis (BCA). It provides a framework for participatory and science-based evaluation processes with combined use of BCA and MCA to support large-scale public decisions. While IMA does not claim to realize an all-inclusive participation scheme, it offers the advantage to improve the quality of decision making through advances in competence and fairness. Its practical application with emphasis on its participatory elements is demonstrated by the case study on the water allocation conflict of the German Spree River, which involves the German capital of Berlin, an important wetland, and the needs to remediate a post-mining landscape.
Keywords: 330; Participation; Multi-criteria analysis; Cost-benefit analysis; River basin management; Integrated Assesment